Organizational Climate Conditions and Work Productivity of State Civil Apparatus Towards the Year of Politics in Gorontalo Province - Agus Hakri Bokingo (Universitas Negeri Gorontalo, 2019)
This study aims to obtain an overview of the organizational climate and its influence on the productivity of ASN work in Gorontalo Province. A total of 46 employees from 8 SKPD (Service Unit Work Unit) were made as speakers and were given questionnaires to obtain information regarding their perceptions regarding organizational climate and measuring how high their work productivity was. The researcher revealed that the organizational climate in the Gorontalo Provincial Government so far was quite conducive. However, towards the political year, according to respondents, there were often several maneuvers carried out by SKPD leaders. Likewise, the work productivity of employees is fairly good. It is proven by the annual performance report that shows the performance achievement of employees who meet the target. Improving work productivity is also influenced by organizational climate conditions. The results of the study show that the organizational climate influences the work productivity of the state civil apparatus in Gorontalo Province. Of the many factors that can affect work productivity, 10.3% of them are influenced by organizational climate factors.Keywords: Organizational Climate, Work Productivity, Year of Politics, ASN